2014
DOI: 10.1371/journal.pone.0103317
|View full text |Cite
|
Sign up to set email alerts
|

Employment among Patients with Multiple Sclerosis-A Population Study

Abstract: ObjectiveTo investigate demographic and clinical factors associated with employment in MS.MethodsThe study included 213 (89.9%) of all MS patients in Sogn and Fjordane County, Western Norway at December 31st 2010. The patients underwent clinical evaluation, structured interviews and completed self-reported questionnaires. Demographic and clinical factors were compared between patients being employed versus patients being unemployed and according to disease course of MS. Logistic regression analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 31 publications
11
86
2
1
Order By: Relevance
“…Similar to other studies with MS patients, patients in this study reported that before the DMT issue, many had to reduce or stop working due to functional cognitive decline related to MS [4][5][6]44,45]. Noting the burden of cost, paperwork, and benefit changes on MS patients trying to obtain DMT, medication advocacy organizations and provider groups have called for system-wide transparency, lower drug prices for DMTs, and policy reforms to assist MS patients with the cost burden of their care [8,46,47].…”
Section: Comparison With Prior Worksupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to other studies with MS patients, patients in this study reported that before the DMT issue, many had to reduce or stop working due to functional cognitive decline related to MS [4][5][6]44,45]. Noting the burden of cost, paperwork, and benefit changes on MS patients trying to obtain DMT, medication advocacy organizations and provider groups have called for system-wide transparency, lower drug prices for DMTs, and policy reforms to assist MS patients with the cost burden of their care [8,46,47].…”
Section: Comparison With Prior Worksupporting
confidence: 85%
“…The financial burden accompanying MS is a central component of the disease experience, ranking second among all chronic conditions in direct costs behind congestive heart failure [3]. In addition to the impact of decreased productivity and unemployment [4][5][6], patients often shoulder the burden of high outof-pocket costs for medications, tests, MRIs, medical equipment, and inpatient/outpatient visits [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,11,12 Ours and a more recent Norwegian study show risk of unemployment increases with age adjusted for disability, at least as measured by EDSS. 25 Interestingly, risk of unemployment increased with age, after adjusting for disability level, education, disease duration or disease course and the loss of a spouse or partner. Thus, these endogenous factors alone do not make employment increasingly difficult to maintain as people with MS age.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study found that the MS population was $3-times more likely to not be employed in a given year than a non-MS population 1 . It has been estimated that 55-80% of individuals with MS retire early after their diagnosis; the work ability varies with MS sub-types 4,5 . Furthermore, the disabling nature of MS imposes a considerable indirect cost burden on employers 6 .…”
Section: Introductionmentioning
confidence: 99%